ETHICAL RESPONSIBILITY OF TRANSLATORS AND INTERPRETERS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
The ethical responsibility of translators and interpreters has become increasingly important in the modern globalized world. Translators and interpreters do not simply transfer words from one language into another; they also mediate cultures, values, and sensitive information. Their work affects diplomacy, healthcare, law, education, media, and international communication. This article investigates the ethical obligations of translators and interpreters through a qualitative review of recent academic literature published within the last five years. The study focuses on the principles of accuracy, confidentiality, neutrality, cultural sensitivity, and professional competence. It also analyzes the ethical challenges created by artificial intelligence and machine translation technologies. The findings demonstrate that ethical decision-making is essential for maintaining trust, fairness, and intercultural understanding. The article concludes that translators and interpreters must continuously develop ethical awareness and professional accountability in order to respond effectively to the changing demands of multilingual societies.